Characterization of gold kiwifruit pectin from fruit of different maturities and extraction methods. (1st January 2015) - Yuliarti, Oni; Matia-Merino, Lara; Goh, Kelvin K.T.; Mawson, John; Williams, Martin A.K.; Brennan, Charles
Highlights: Gold kiwifruit pectin was isolated at different maturities and extraction methods. Pectins isolated from main harvest fruit were rich in galacturonic acid content. Gold kiwifruit pectin was classified as high-methoxyl pectin. Enzymatic treatment gave the highest pectin yield but lower in molecular weight. Abstract: Studies on gold kiwifruit pectins are limited. In this work, the characterization of pectin isolated from two different stages of maturity of gold kiwifruit, namely early harvested fruit (EHF) and main harvested fruit (MHF) isolated by three methods (acid, water, enzymatic) was carried out. Pectins isolated from MHF were higher in galacturonic acid content (52–59% w/w) and weight-average molecular weights ( Mw, 1.7–3.8 × 10 6 g/mol) compared with EHF pectins (29–49% w/w and 0.2–1.7 × 10 6 g/mol respectively). Enzymatic treatment gave the highest yield but lowest in Mw, viscosity and mechanical spectra for both maturities. The pectin of both maturities was classified as high-methoxyl pectin with the degree of esterification ranged from 82% to 90%. Water-extracted MHF pectin molecules had the highest RMS radius (182.7 nm) and Mw (3.75 × 10 6 g/mol). The water extraction method appeared to retain the native state of pectin molecules compared with acid and enzymatic extraction methods based on the Mw and viscosity data.